Pemberdayaan Masyarakat Berbasis Pendidikan Kesehatan di Dusun Dasan Geres Kabupaten Lombok Barat - Ni Luh Anita Yustitie Sari (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Public health is one of the important indicators in sustainable development. However, in rural areas such as Dasan Geres Hamlet, Ranjok Village, Gunung Sari District, West Lombok Regency, various health problems are still found related to the low level of public knowledge and awareness. This community service activity aims to empower the community based on health education through participation, with a focus on improving Clean and Healthy Living Behavior (CHLB), understanding of balanced nutrition, and preventing infectious diseases. The methods used include interactive education and counseling based on target groups (children, housewives, and the elderly). The results of the activity showed a significant increase in community understanding of basic health issues. This activity proves that an educational-participatory approach can be an effective strategy in empowering rural community health in a sustainable manner.